Analysis of Facade Implementation with Acceleration Method In The Development of Phase 4 of Supermall Pakuwon Indah of Benson Tower 6 Surabaya - Prayogo, Renaldy Eka; Nasihien, Ronny Durrotun (Yayasan Ahmar Cendekia Indonesia, 2020)
The implementation of the façade with the acceleration method in the construction of phase 4 of Supermall Pakuwon Indah of Benson Tower 6 Surabaya is possible because of several aspects such as the delays in the work because the land is not ready. To analyze the acceleration method using the Ms Project program. From the results of the analysis with the acceleration method of adding work hours (overtime work), the duration of the implementation was 282 days, causing an increase in direct costs from Rp. 15,610,242,664.00 to Rp. to Rp. 17,661,323,855.34. And with the method of accelerating the addition of resources (labor & equipment), the duration of implementation was 287 days, causing an increase in direct costs from Rp. 17,410,735,885.96. After analyzing the acceleration of the duration of the implementation, it can be seen that the results of the study of the implementation of the façade with the acceleration method in the construction of phase 4 of Supermall Pakuwon Indah of Benson Tower 6 Surabaya is more effective using the acceleration method of adding work hours (overtime work) because the duration of the implementation is faster than using acceleration time with the method of increasing resources (labor and tools).